Locked nucleic acid (LNA): A modern approach to cancer diagnosis and treatment - Kamali, Mohammad Javad; Salehi, Mohammad; Fatemi, Somayeh; Moradi, Fereshteh; Khoshghiafeh, Azin; Ahmadifard, Mohamadreza (Experimental cell research, 2023)
Cancer is responsible for about one in six deaths in the world. Conventional cancer treatments like chemotherapy, radiotherapy, and surgery are associated with drug poisoning and poor prognosis. Thanks to advances in RNA delivery and target selection, new cancer medicines are now conceivable to improve the quality of life and extend the lives of cancer patients. Antisense oligonucleotides (ASOs) and siRNAs are the most important tools in RNA therapies. Locked Nucleic Acids (LNAs) are one of the newest RNA analogs, exhibiting more affinity to binding, sequence specificity, thermal stability, and nuclease resistance due to their unique properties. Assays using LNA are also used in molecular diagnostic methods and provide accurate and rapid mutation detection that improves specificity and sensitivity. This study aims to review the special properties of LNA oligonucleotides that make them safe and effective antisense drugs for cancer treatment by controlling gene expression. Following that, we go over all of the molecular detection methods and cancer treatment antisense tactics that are possible with LNA technology.